URIC ACID AS A RISK FACTOR FOR CARDIOVASCULAR DISEASE. A PROSPECTIVE OBSERVATIONAL STUDY. (June 2018) - Kallistratos, M.; Giannitsi, S.; Poulimenos, L.; Miaris, N.; Koukouzeli, A.; Khashlok, L.A.; Kouremenos, N.; Tsinivizov, P.; Kontogiannis, N.; Chamodraka, E.; Athanasiou, D.; Kalogeris, A.; et al.
Abstract : Objective: Hyperuricaemia is associated with many traditional cardiovascular risk factors such as arterial hypertension, diabetes and dyslipidaemia. Our purpose was to investigate the relationship of Serum Uric Acid (SUA) levels with the ten – year risk of fatal cardiovascular disease. Design and method: We prospectively enrolled 568 hypertensive patients (mean age 63 ± 10 years) presented for evaluation in the hypertension clinic. In all subjects routine blood chemistry, including SUA determination, echocardiographic examination, office and 24 h ambulatory blood pressure (BP) monitoring were obtained along with data regarding lifestyle habits (smoking, alcohol consumption and exercise). The ten – year risk of fatal cardiovascular disease was evaluated by using the SCORE chart for countries with low CVD risk based on the following risk factors: age, sex, smoking, systolic blood pressure, and total cholesterol. Results: Mean average 24 hours systolic blood pressure (SBP) was 132 ± 15 mmHg, mean 24 hours average diastolic blood pressure (DBP) was 77 ± 10 mmHg while mean total cholesterol was 198 ± 39 mg/dl. Spearman analysis showed that SUA levels were significantly and positively associated with the average 24 hours systolic blood pressure levels (rs = 0.092, p < 0.05 for SBP) but not with diastolic BP levels (rs = 0.06, p > 0.05). Furthermore the kruskal Wallis analysis revealed that SUA levels were significantly associated with 10year risk of fatal cardiovascular disease (p < 0.001). Specifically, patients with 10year risk < 1%, 1–5%,  > 5%, had SUA levels 4, 8 ± 0.1 mg/dl, 5, 4 ± 0.5 mg/dl and 6, 0 ± 0.1 mg/dl respectively (Z: −7, 7 p < 0.001). Conclusions: Subjects with lower SUA levels presented lower BP levels as well as 10year risk of fatal cardiovascular disease and vice versa. SUA levels were significantly associated with systolic blood pressure levels and 10year risk of fatal cardiovascular disease.